A functional interlayer as a polysulfides blocking layer for high-performance lithium–sulfur batteries. (4th January 2018) - Yin, Lingxia; Dou, Hui; Wang, Aixiu; Xu, Guiyin; Nie, Ping; Chang, Zhi; Zhang, Xiaogang
Abstract : Self-standing polyaniline–graphene oxide (PANI–GO) interlayer inhibits the shuttle effect by the physical barrier and chemisorption, improving the electrochemical performance for Li–S batteries. Abstract : A new Li–S battery with a polyaniline–graphene oxide (PANI–GO) membrane sandwiched between a sulfur cathode and a separator shows high cycling stability and enhanced rate performance. The initial specific capacity is 1261 mA h g −1 at 0.5C and the capacity retention is 73.0% after 150 cycles. The excellent electrochemical performance can be attributed to the new cell configuration. Specifically, the PANI–GO membrane can not only effectively mitigate the diffusion of lithium polysulfides to the negative electrode by a chemical interaction between the imine group (–N) of the quinoid ring and polysulfides, but also improve sulfur utilization due to its conductive networks.